Historical Significance Of Research Conducted At The Department Of Central Asian Archaeology - Komiljon Mirzayev (Genius Journals, 2024)
This article analyzes the important research conducted at the Department of Central Asian Archaeology and their historical significance. The article examines how these studies shed new light on the history of Central Asia and contributed to the development of international archaeological science. It also assesses the place of archaeological monuments discovered and studied by the department in regional and global history. The information about cultural connections and historical processes identified as a result of the research reveals the versatility and depth of the history of Central Asia.
Keywords: Central Asia; archaeology; historical research